APLIKASI PENCARIAN LOKASI KOST BAGI MAHASISWA DI KOTA SERANG MENGGUNAKAN ALGORITMA UCS - Darip, Mochammad; Auliana, Sigit (Politeknik Bisnis Indonesia, 2024)
The availability of boarding houses or accommodations near campuses is often limited, particularly for universities located in urban areas. This scarcity leads to intense competition among students for strategic housing options. In Serang City, the capital of Banten Province, the student population increases every year, especially from outside the region. However, this growth creates a new problem: the limited availability of strategically located housing. To address this, an innovative solution is proposed by applying the Uniform Cost Search algorithm to identify optimal boarding house locations for students. The UCS algorithm efficiently determines the best routes or locations at minimal cost by considering distance and access to public transportation. This study employs a quantitative approach and simulates the UCS algorithm. The UCS model is used to design an application with a user interface created using Figma and developed in Dart. The implementation results show that the UCS algorithm effectively identifies the nearest accommodation. Simulations revealed that Wisma Mina Kost is the most strategic location, about 260 meters from the main road. Additionally, the application provides public transport route details, such as route 01 and travel paths. This information serves as a valuable recommendation for students seeking strategic accommodations in Serang City.